ANALISIS FAKTOR YANG MEMPENGARUHI PETANI MENJUAL KOPI ROBUSTA DALAM BENTUK GLONDONG MERAH DI DESA PUJUNGAN KECAMATAN PUPUAN KABUPATEN TABANAN - Engelbertus Rolanto Jebaru; Ni Gst.Ag.Gde Eka Martiningsih; i Made Budiasa (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2022)
This thesis is entitled Analysis of Factors Affecting Farmers Selling Robusta Coffee in the Form of Red Loons in Pujungan Village, Pupuan District, Tabanan Regency. The purpose of this research is to find out the factors that influence farmers to sell robusta coffee in the form of red logs and to find out how the income differences of farmers selling robusta coffee in the form of red logs and coffee beans are in Pujungan Village, Pupuan District, Tabanan Regency. This research was conducted from October to November 2021, located in Pujungan Village, Pupuan District, Tabanan Regency. This research was conducted with 12 farmers as respondents in Pujungan Village, using the census technique. The data analysis method used is descriptive method with Kendall S test, income difference analysis with (TR) then the hypothesis is tested using t test. The results of this study indicate that (1) the factors that influence farmers to sell robusta coffee in the form of red logs are the age of the plant, the number of requests, labor, weather conditions, and time efficiency. (2) The income in the form of coffee beans is greater than in the form of red logs, where the average income for selling coffee beans is Rp. 9.690.272/year or equivalent to Rp 807.522/month while the average income for red logs is Rp. 7.937.654/year or equivalent to Rp 661.471/month.